Meningkatkan efektivitas pembelajaran di era digital melalui pelatihan pengembangan video pembelajaran interaktif - Ulumi, Desepta Isna; Sujaini, Herry; Perwitasari, Anggi; Novriando, Haried (Universitas Hamzanwadi, 2023)
Effective teaching in the digital era poses a major challenge in education, especially in elementary schools. This study highlights the importance of interactive learning media in enhancing teaching quality. Utilizing methods of presentation, discussion, and mentoring, this training targeted 50 elementary school teachers at SDN 39 and SDN 08 Sungai Kakap. The main focus was on creating educational videos using Microsoft PowerPoint, a software commonly used by teachers. The training content included the definition of educational videos, steps in video creation, tips for making engaging videos, and using PowerPoint for educational purposes. Pre-tests and post-tests were conducted to measure participants' understanding before and after the training. Results showed a significant improvement in understanding and skills in creating educational videos, with average pre-test scores rising from 54 to 93 in post-tests. Participants realized that PowerPoint is not only for presentations but also an effective tool for creating engaging and efficient educational videos. This research affirms that technology-based interactive learning, such as PowerPoint educational videos, enhances teachers' enthusiasm and student engagement, and supports teaching effectiveness in elementary schools. The main conclusion is that educational technology training like this is crucial for enhancing teachers' creativity and the quality of learning in the digital era.